(untitled) (Journal of the College of Basic Education, 2023)
Praise be to God, Lord of the Worlds, and prayers and peace be upon the Master of Messengers, our master Muhammad and his family and companions:After that, the interpretation of the Islamic sects receives the attention of researchers and scholars, especially if this sect whose interpretation is to be defined was one of the first sects of Islam to originate and deviate from the white argument. By opinion, he was seen with some dissatisfaction at the beginning, in addition to the extinction of most of the Kharijite sects, and only the Ibadites remained, and this thing prompted me to rely on the stomachs of books to extract the opinions of the Kharijites and not to rely on the sources of the Kharijites from their perspectives because of the loss of those sources.